PENGARUH KONTEN VIRAL AVOSKIN PADA MEDIA SOSIAL TIKTOK TERHADAP PERILAKU KONSUMTIF BAGI PENGGUNA TIKTOK DI KOTA MAKASSAR - Micha Selya Malacopo; Andriansyah Andriansyah (Journal of Communication Sciences (JCoS), 2022)
This study aims to determine the effect of Avoskin's viral content on social media tiktok on consumptive behavior of tiktok users in Makassar City. The method in this study uses a type of quantitative research. The population in this study is the people of Makassar City totaling 512,764 people aged 15-34 years. The sample in this study amounted to 100 people who were determined by the Slovin formula with a 10% inaccuracy allowance with data collection techniques through questionnaires distributed by researchers and data processing using simple regression analysis with the help of the SPSS ver 25 program. The results showed that the correlation test value was 0.461, the calculated value of the t test was 5.139 > ttable 1.983 and a significance value of 0.000 <0.05. Then the coefficient of determination is 0.212 or 21.2% as seen from R Square while the remaining 78.8% is influenced by other factors. From the results of the data analysis it can be concluded that there is an influence of Avoskin's viral content on the social media tiktok on consumptive behavior of tiktok users in Makassar City.